The Directive Acts in Joker 2019 Movie - Willy Sitanggang; Afriana Afriana (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This article represented the study of pragmatic to investigate directive act. The purpose of investigation is to find out the types of directive acts on movie “Joker 2019”. The researchers applied theory ofAllan (1997)about directive act. The researchdesignpresented in  the qualitative method.In collecting the data, the researchersappliedobservational method and note-taking technique. In analyzing the data,the researchers applied pragmatic identity method and classify technique by sudaryanto. In the analysis, the researchers found the types of directive speech act. This research had 15 data from types of directive speech acts which was separated into requestives (4 data), requirements (2 data), questions(2 data), prohibitives (2 data), permissives (1 data) and advisories.